2009
DOI: 10.1007/s11858-009-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Good mathematics instruction in South Korea

Abstract: There have been only a few studies of Korean mathematics instruction in international contexts. Given this, this paper describes in detail a sixth grade teacher's mathematics instruction in order to investigate closely what may be counted as high-quality teaching and learning in Korea. This paper then discusses several key characteristics of good mathematics instruction along with some background information on Korean educational practice. This paper concludes with remarks that good mathematics instruction may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…The results showed that Korean teachers perceived the importance of essential concepts and their connections in mathematics teaching. This result is aligned with the most salient characteristic of Korean classroom expertise, which is an emphasis on mathematical content (Pang, 2009). However, the teachers also thought that effective mathematics teaching includes enhancement of mathematical processes, such as problemsolving, communication, and reasoning, as well as consideration of students' individual differences and concerns.…”
Section: Discussionsupporting
confidence: 63%
“…The results showed that Korean teachers perceived the importance of essential concepts and their connections in mathematics teaching. This result is aligned with the most salient characteristic of Korean classroom expertise, which is an emphasis on mathematical content (Pang, 2009). However, the teachers also thought that effective mathematics teaching includes enhancement of mathematical processes, such as problemsolving, communication, and reasoning, as well as consideration of students' individual differences and concerns.…”
Section: Discussionsupporting
confidence: 63%
“…The approach of exemplary lesson development has been used in the Chinese mainland to improve the quality of mathematics instruction (Huang & Bao, 2006). Instructional contests are organized to promote quality mathematics instruction in several education systems in East Asia (e.g., Lin, 2008;Pang, 2008;Shimizu, 2008). Master teachers also play an important role in improving mathematics instruction in the Chinese mainland (e.g., Li, Huang, Bao, & Fan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of the video-recorded lessons taught by an elementary mathematics teacher over a year in Korea, Pang (2009) found that using the guided investigations was a major feature of her lessons, in which the teacher used one specific problem to elicit students' multiple solutions and then carefully orchestrated classroom discussion to lead the students towards higher-level mathematics thinking skills. The TIMSS 1995 video study that analyzed the lessons taught in 8th grade Japanese classrooms revealed that Japanese teachers went into greater depth to develop students' mathematical concepts and procedures leading to a focus on reasoning and proof in their lessons (Hiebert & Stigler, 2000;Stigler et al, 1999).…”
Section: Empirical Basesmentioning
confidence: 99%